Budget-impact analysis of health care interventions : a practical guide - Mauskopf, Josephine; Earnshaw, Stephanie R.; Brogan, Anita Jean; Wolowacz, Sorrel; Brodtkorb, Thor-Henrik (ADIS, 2017)
The first of its kind for budget-impact analysis, this comprehensive guide provides clear and concise instructions for evaluating the impact that new pharmaceuticals will have on the budget for a specific jurisdiction. The book demonstrates how to create a budget-impact analysis using a simple six-step process that is consistent with current guidelines for these analyses. Examples and exercises for each chapter afford an opportunity to practice the six-step process in practical applications. The book progresses from a framework for budget impact analyses to an in-depth review of components and how to develop and present these in software applications and reports. Critical considerations such as uncertainty analysis and validation, and considerations for alternate interventions, such as vaccines and diagnostics, are also covered. This book is a "must have" for the builder and budget holder, with builders benefiting from instructions to identify and estimate all necessary variables and budget holders receiving a guide to what should be included in the analyses they assess.